DNA methylation dynamics during B cell maturation underlie a continuum of disease phenotypes in chronic lymphocytic leukemia - Oakes, Christopher C.; Zenz, Thorsten (Nature genetics, 2016)
Christoph Plass, Christopher Oakes and colleagues study genome-wide DNA methylation dynamics during B cell maturation and the pathogenic role of transcription factor dysregulation in chronic lymphocytic leukemia (CLL). By comparing normal and malignant B cells, they find that tumors derive from a continuum of maturation states, which correlate with different clinical outcomes.